ByzRev 02.2020.001: Petra Melichar, Empresses of Late Byzantium: Foreign Brides, Mediators and Pious Women - Goldwyn, Adam (The Byzantine Review, 2020)
Petra Melichar, Empresses of Late Byzantium: Foreign Brides, Mediators and Pious Women. Berlin: Peter Lang 2007. 497 pp. – ISBN: 978-3-631-74667-7 (€ 96,95)